Single image defogging based on fusion strategy - OFan GU; Jin TANG; Zi-xing CAI (Tongxin xuebao)
To effectively enhance the degraded foggy image, a single image defogging algorithm based on fusion strategy was proposed. The strategy does not require the atmospheric scattering model or scene structure, only needs the original degraded image to derive the inputs and weight maps. The function of the two inputs is to correct color and enhance con-trast, and the three weight maps improve the detail information of the regions in dense fog. All the inputs and weight maps are fused by using fusion strategy to produce a high-contrast and vivid fog removal image. Besides, an index for defogging effect assessment is also proposed from the perspective of human visual perception, which provides a new so-lution to the problem of single image defogging and its effect assessment. Experimental results show that the proposed fusion strategy method can better improve the image quality for various foggy images.